Effect of NaOH Concentration Toward the Characteristics of Activated Natural Zeolite from Blitar – East Java - Andi Nafis An Naafi; Rachmat Triandi Tjahjanto; Yuniar Ponco Prananto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
This study discusses the activation of natural zeolite from Blitar City – East Java using NaOH solution (0.5 M and 1.0 M). Characteristics of unactivated and activated zeolites were also investigated, as well as the effect of the activator (NaOH solution) on functional groups, element composition, pore size, specific surface area, and total pore volume. FTIR spectroscopy, XRF, and gas physisorption were conducted to support the study. Experimental data showed that: (1) the major functional groups were observed at 1250-780 cm-1 in the infrared spectra, in which the unactivated and the activated zeolite were not significantly different; (2) the elemental composition of zeolite (Si and Al) tended to decrease after the activation process; (3) the pore size of the activated zeolite increased while the surface area and total pore volume decreased. Based on this study, activated zeolite (AZB-1.0) showed the optimum result: the pore size increased by 4.12847 nm, and the total pore volume did not decrease significantly by 0.04987 cc/g.